COOPERATIVE R&D WITH DIFFERENTIATED PRODUCTS IN VERTICALLY RELATED INDUSTRIES - Parisa Pourkarimi; Gamal Atallah (Economic Review)
This paper studies the impact of cooperative R&D on innovation, welfare, and profitability in vertically related industries with differentiated products. The model incorporates two vertically related industries, with horizontal spillovers within industries and vertical spillovers between them. Upstream firms produce a homogeneous intermediate good, while downstream firms provide differentiated products. Three types of R&D cooperation are studied: no cooperation, horizontal cooperation, and vertical cooperation. The comparison of cooperation settings in terms of R&D and profitability shows that although vertical cooperation yields higher innovation and welfare, it may lead to over–investment in R&D.